Quasi adulti? I riti di passaggio nella prosa dei “giovani narratori” italiani della fine del Novecento - Kornacka, Barbara (Romanica Silesiana)
The aim of the article is to show some analogies between the rites of passage — of the initiation to the adult life — in the traditional or archaic societies, as described by A. Gennep and V. Turner (three phases: separation, transition and reincorporation), and the behavior, actions, gestures and reactions of young characters in analyzed literature. The young protagonists instinctively follow almost identical pattern of the first two phases of the rites of passage. The third one may be missing, because of the “emerging adulthood”, i.e., a new stage of becoming adult, as proposed by J.J. Arnett. The remarkable difference is also that the young protagonists are never accompanied by the elders, as it happened in the archaic or traditional societies. Key words: contemporary Italian prose, young writers, rites of passage